KETERLAMBATAN DIAGNOSIS KANKER OVARIUM DAN DAMPAKNYA TERHADAP PROGNOSIS PASIEN DI NEGARA BERKEMBANG - Dewi; Ernawati (Rena Cipta Mandiri, 2025)
This study is a systematic review of 10 international journals published between 2020 and 2025, examining the diagnosis, treatment, and survival of ovarian cancer patients, particularly in low- and middle-income countries (LMICs). The findings indicate that delayed diagnosis and treatment are the primary causes of poor survival rates. Other contributing factors include limited access to healthcare services, variations in histological subtypes, and socioeconomic and geographical disparities. In Indonesia, the average survival time for ovarian cancer patients is only five months, significantly lower than the global average. In Sub-Saharan Africa, the five-year survival rate is approximately 45%, with notable variation between countries. The study also identifies that moderate delays in surgery during the early stages do not necessarily worsen outcomes if clinical management is properly conducted. This review recommends several strategic interventions, such as enhancing early detection, strengthening referral systems, increasing public awareness of early symptoms, and improving the capacity of oncology services. Reducing ovarian cancer mortality requires collaboration among governments, healthcare providers, and communities to expand equitable access to quality cancer care in developing countries.